2005
DOI: 10.1128/jcm.43.5.2194-2200.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Borrelia burgdorferi Sensu Lato Strains Isolated from Specimens Obtained Simultaneously from Two Different Sites of Infection in Individual Patients

Abstract: The aim of the present study was to analyze and compare Borrelia strains isolated from two different specimens obtained simultaneously from individual patients with Lyme borreliosis. Fifty such patients and 50 corresponding pairs of Borrelia isolates (100 low-propagated strains) were subjected to genotypic and phenotypic analysis, including pulsed-field gel electrophoresis for species identification and plasmid profile determination and protein profile electrophoresis for the assessment of the presence and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…So far, there have been no reports of cultivation of more than one Borrelia genospecies from a single infection site, such as from erythema migrans; however, different genospecies have been cultivated from different body sites in individual patients. No evidence exists for an ambiguous course that might impede the clinical diagnosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…So far, there have been no reports of cultivation of more than one Borrelia genospecies from a single infection site, such as from erythema migrans; however, different genospecies have been cultivated from different body sites in individual patients. No evidence exists for an ambiguous course that might impede the clinical diagnosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental studies on B. burgdorferi are frequently carried out using a single strain, field studies have shown that mixed infections with different B. burgdorferi genotypes occur in ticks and mammalian reservoir hosts (46)(47)(48)(49). In humans, different strains have been isolated from individual Lyme disease patients (50,51). The observed lack of host barriers to dissemination in mice may contribute to the frequency of heterogeneous infections observed in environmental studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results, indicating double infections, are somewhat surprising but corroborate previous findings. Information obtained predominantly from PCR [20][21][22] but also from culture results [15,23] indicates that an individual patient with Lyme borreliosis may simultaneously harbor more than one Borrelia strain of the same species and even more than one Borrelia species.…”
Section: Discussionmentioning
confidence: 99%